Penurunan Tingkat Kecacatan Produk di CV. Omega Plastics - Wijaya, Robby Hadi; Rahardjo, Jani (Jurnal Titra, 2013)
CV Omega Plastics is one of the companies which produced various plastic products for household. Reject rate for juventus shelf tray was 7%. The biggest reject rate was on injection process. Those are holes and bend which are from pareto chart analysis. Fishbone diagram analysis is used to find the root cause of holes and bend defect. The main cause of holes and bend defect is injection machine setting. Pres and cycle time are the factors which influence production output. Failure Mode and Effect Analysis method is used to analyze the improvement to refuse reject rate. The improvement suggested are materials quality, machine setting, work instruction, and machine control schedule, those improvement can reduce 2% of juventus shelf tray reject rate.